Ticlopidine decreases the in vivo activity of CYP2C19 as measured by omeprazole metabolism - Tateishi, Tomonori (Blackwell Science Inc, 1999)
AIMS: To examine the effect of ticlopidine administration on the activities CYP2C19 and CYP3 A in vivo using omeprazole as a model substrate. METHODS: A single dose of 40 mg omeprazole was administered orally with or without ticlopidine (300 mg daily for 6 days) to six Japanese extensive metabolisers with respect to CYP2C19. Blood samples were taken for the measurement of plasma concentrations of omeprazole, 5-hydroxyomeprazole and omeprazole sulphone. RESULTS: Ticlopidine administration increased omeprazole C(max) (1978±859/ 3442±569 (control phase/ticlopidine phase, nm)) and decreased the oral clearance of omeprazole (CL/F; 25.70±16.17/10.76±1.16 (control phase/ticlopidine phase, l h(−1))) significantly. The 5-hydroxyomeprazole to omeprazole AUC ratio (0.817±0.448/0.236±0.053 (control phase/ticlopidine phase)) and the 5-hydroxyomeprazole to omeprazole sulphone AUC ratio (1.114±0.782/0.256±0.051 (control phase/ticlopidine phase)) were decreased significantly after ticlopidine administration. The decrease in omeprazole CL/F and the 5-hydroxyomeprazole to omeprazole AUC ratio correlated significantly with their respective absolute values when the drug was given alone. The decrease in CL/F following ticlopidine administration correlated with that in the 5-hydroxyomeprazole to omeprazole AUC ratio. CONCLUSIONS: These findings suggest that ticlopidine inhibited the in vivo activity of CYP2C19, but not, or to a lesser extent CYP3 A4, and that the magnitude of inhibition by ticlopidine is related to the in vivo activity of CYP2C19 before inhibition.